2016
DOI: 10.1111/poms.12548
|View full text |Cite
|
Sign up to set email alerts
|

Dual Sourcing Under Random Supply Capacities: The Role of the Slow Supplier

Abstract: S ourcing from multiple suppliers with different characteristics is common in practice for various reasons. This paper studies a dynamic procurement planning problem in which the firm can replenish inventory from a fast and a slow supplier, both with uncertain capacities. The optimal policy is characterized by two reorder points, one for each supplier. Whenever the pre-order inventory level is below the reorder point, a replenishment order is issued to the corresponding supplier. Interestingly, the reorder poi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 45 publications
0
21
0
Order By: Relevance
“…Different from Ciarallo et al (), she found that the optimal policy is affected by the uncertain capacity. Tan et al () studied the dynamic procurement planning problem in which a firm can replenish from a fast and a slow supplier, both with random capacity. They showed that the slower supplier plays an important role in mitigating the stock‐out risk when demand and capacity uncertainty are present.…”
Section: Related Literaturementioning
confidence: 91%
See 1 more Smart Citation
“…Different from Ciarallo et al (), she found that the optimal policy is affected by the uncertain capacity. Tan et al () studied the dynamic procurement planning problem in which a firm can replenish from a fast and a slow supplier, both with random capacity. They showed that the slower supplier plays an important role in mitigating the stock‐out risk when demand and capacity uncertainty are present.…”
Section: Related Literaturementioning
confidence: 91%
“…It is possible for manufacturers to mitigate and relax their capacity constraints by some measures, which however would incur a higher cost (Chen & Hu, ; Huggins & Olsen, ; Wang, Gilland, & Tomlin, ). The strategies that can be used to handle uncertain supply capacity, as well as the corresponding trade‐off between cost and supply reliability, have been explored in the recent literature (eg, Chen & Guo, ; Tan, Feng, & Chen, ). In addition, the recent literature has also shown that the retailer can provide incentives or work with the manufacturer/supplier to enhance capacity reliability (Tang, Gurnani, & Gupta, ; Wang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…It is possible for manufacturers to mitigate and relax their capacity constraints by some measures, which however would incur a higher cost (Chen & Hu, 2017;Huggins & Olsen, 2003;Wang, Gilland, & Tomlin, 2010). The strategies that can be used to handle uncertain supply capacity, as well as the corresponding trade-off between cost and supply reliability, have been explored in the recent literature (eg, Chen & Guo, 2014;Tan, Feng, & Chen, 2016). In addition, the recent literature has also shown that the retailer can provide incentives or work with the manufacturer/supplier to enhance capacity reliability (Tang, Gurnani, & Gupta, 2014;Wang et al, 2010).…”
Section: Background and Motivationmentioning
confidence: 99%
“…Different from Ciarallo et al (1994), she found that the optimal policy is affected by the uncertain capacity. Tan et al (2016) studied the dynamic procurement planning problem in which a firm can replenish from a fast and a slow supplier, both with random capacity. They showed that the slower supplier plays an important role in mitigating the stock-out risk when demand and capacity uncertainty are present.…”
Section: Related Literaturementioning
confidence: 99%
“…Parlar and Wang (), Anupindi and Akella (), and Swaminathan and Shanthikumar () offer the use of multiple suppliers (each with random yield) to lessen the risk. In recent years, Tomlin (), Chen, Zhao, and Zhou (), Kouvelis and Li (), and Tan, Feng, and Chen () offer the use of back‐up/emergency suppliers to mitigate the risk of random yield.…”
Section: Literature Reviewmentioning
confidence: 99%